EVALUASI PELAKSANAAN SUPERVISI AKADEMIK DAN TINDAK LANJUT HASIL SUPERVISI DALAM MENINGKATKAN PROFESIONALISME GURU - Ririn Mu'tamiroh, Siti; Ahmad Manshur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the implementation of academic supervision and follow-up on its results in improving the quality of education, particularly in developing teacher competency and professionalism. Follow-up on supervision results is an integral part of the teacher development process so that evaluation results can have a tangible impact on the quality of learning. This follow-up on academic supervision aims to produce teachers and educators capable of educating and educating the nation's next generation while creating a comfortable and welcoming school environment. This article uses a qualitative research method with a literature review approach, collecting data from existing research journals relevant to the proposed idea. The results indicate that effective academic supervision requires continuous planning, implementation, evaluation, and follow-up. Follow-up on supervision results can be achieved through coaching, training, professional discussions, and mentoring teachers in the learning process. Various studies indicate that academic supervision accompanied by effective follow-up can improve teachers' pedagogical, professional, social, and personal competencies. Furthermore, the success of academic supervision is influenced by the supervisor's skills, effective communication, and support from the school environment.